Pelayanan Pendidikan dalam Menangani Implikasi Bullying Melalui Sosialisasi Kepada SDN Penikenek, Kecamatan Nagawutung, Kabupaten Lembata - Imelda Jawa Lembu; Kresensia Santrika; Arnoldus Suban Hayon; Johan Semuel Bonat Tamonob; Frans Nyong; Innosensia I.E. Ndiki Satu (Lembaga Pengembangan Kinerja Dosen, 2024)
Education plays an important role in shaping a child's character and personality. Schools as formal educational institutions are not only tasked with imparting knowledge, but are also a place for the formation of social values, morals and behavior. (Cahyani et al., 2021) However, the reality shows that schools are often places where negative behavior emerges, one of which is bullying. The method used in this community service activity uses a participatory method by involving the school in the continuity of socialization activities. The approach taken is to direct and explain efforts to deal with the implications of bullying through the elementary school environment. The place of service was carried out at SDN Penikenek, Nagawutung District, Lembata Regency involving research subjects consisting of the Principal, teachers, students, grades 1-6. Community service activities with the title